"Insomnia in Patients Diagnosed with Multiple Sclerosis: The Effect of Medicinal Cannabis - a systematic review." - Pedro Manuel Vilaça Gomes (2022)
Background: When compared to the general population, people with multiple sclerosis (PwMS) have a higher prevalence of sleep disturbances. In addition, they report frequent use of cannabis mainly due to pain, spasticity and insomnia. In fact, a solution for oral transmucosal delivery containing a mixture of cannabis extracts has been authorized to treat muscle spasticity in several countries. In this view, the present systematic review aims to clarify whether medical cannabis has any effect on insomnia in patients previously diagnosed with multiple sclerosis. Methods: A literature search was conducted on the PubMed, Scopus and Web of Science databases from November 30 to December 3 and data were collected by the two authors using an Excel® sheet. The National Institute of Health (NIH) criteria were used as a quality assessment tool for observational studies, while the Risk of Bias 2 (RoB 2) tool was used to assess the quality of the randomized controlled trials. Results: The database search yielded 82 articles. Five studies were included, two of which were observational transversal studies while the other three were randomized controlled trials, representing a total of 579 patients and 366 surveys answered. Regarding the individual risk of bias of the studies, the two non-randomized studies came out as fair and the randomized studies all revealed an overall low risk of bias. The five studies included showed trends in favor of active treatment regarding the therapeutic management of sleep disturbances, with patients reporting they fall asleep faster and more easily when being administered medicinal cannabis, with a general benefit from cannabis use in insomnia treatment. Besides the perceived positive effect of medicinal cannabis in sleep disturbances, the included articles demonstrated it also helped alleviate other MS-related symptoms such as pain and spasticity, which may contribute to better and more effective management of secondary insomnia. Furthermore, all the studies referred patients under active treatment experienced minor or mild adverse events, mainly dizziness, disturbances in attention, memory problems or nausea. Nonetheless, PwMS who use medicinal cannabis refer subjective symptomatic benefit across an array of symptoms in MS and the medication was well-tolerated across the five studies. Conclusion: Medicinal cannabis appears to have a beneficial effect on sleep pattern regarding patients with multiple sclerosis, whether directly or by attenuating other MS-related symptoms such as pain or muscle spasticity.